2021
DOI: 10.3390/polym14010163
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential to Repurpose Flexible Moulded Polyurethane Foams as Acoustic Insulators

Abstract: Polyurethane flexible foams are widely used for a variety of applications to improve comfort and durability. Their long-term frequent use inevitably leads to the generation of waste that needs to be treated. The recycling and reuse of polyurethane waste are essential to achieve an environmentally friendly economy. The present study investigates the potential to reuse and repurpose flexible polyurethane foam from automotive seat cushion waste materials. Flexible foams were prepared with different hardnesses usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Its purpose is to lift the column that can move up and down freely within the range of travel. Polyurethane cushion material should be selected, which has light weight, good compression resistance, simple installation, good buffering effect, impact resistance, no noise, no spark in the buffering process, good explosion-proof, safe, reliable and stable [20][21][22][23]. There are three buffer pads on the frame of the mechanism: (a) at the steps inside the cylinder body, the purpose is to prevent the impact of the lifting column movement in place, which can prolong the service life of the lifting column and cylinder body; (b) The flange in the middle of the cylinder body is to prevent the impact of the retaining ring on the lifting column and the flange of the frame when the electricity is energized; (c) A cushion is installed on the base to prevent the impact of the sliding rod and the base when power is cut off.…”
Section: Framementioning
confidence: 99%
“…Its purpose is to lift the column that can move up and down freely within the range of travel. Polyurethane cushion material should be selected, which has light weight, good compression resistance, simple installation, good buffering effect, impact resistance, no noise, no spark in the buffering process, good explosion-proof, safe, reliable and stable [20][21][22][23]. There are three buffer pads on the frame of the mechanism: (a) at the steps inside the cylinder body, the purpose is to prevent the impact of the lifting column movement in place, which can prolong the service life of the lifting column and cylinder body; (b) The flange in the middle of the cylinder body is to prevent the impact of the retaining ring on the lifting column and the flange of the frame when the electricity is energized; (c) A cushion is installed on the base to prevent the impact of the sliding rod and the base when power is cut off.…”
Section: Framementioning
confidence: 99%
“…In order to improve this performance, the aluminum alloy sheet structure can be filled with polyurethane foam material, so that the thin-walled structure has higher strength and energy absorption performance. Usually, polyurethane foam [ 1 ] is formed by foaming process and bonded with aluminum alloy panel. However, in the process of bonding, due to immature technology, improper operation and other reasons, various defects will appear on the bonding surface such as poor bonding, pores and so on, which directly affect the safety and reliability of the whole structure.…”
Section: Introductionmentioning
confidence: 99%
“…The multi-stage reuse of flame retardant FPUF is a utilization method that considers safety and the environment. 30,31 Specifically, the inherent physical properties of FPUF, especially the porous structure with a high specific surface area, are utilized for reuse in other fields after FPUF waste. For instance, Si et al 32 reported that dealing the FPUFW with tung oil/organic silicon oil to endow FPUFW with excellent oil absorbency and successfully realize the reuse of FPUFW.…”
Section: Introductionmentioning
confidence: 99%
“…The multi‐stage reuse of flame retardant FPUF is a utilization method that considers safety and the environment 30,31 . Specifically, the inherent physical properties of FPUF, especially the porous structure with a high specific surface area, are utilized for reuse in other fields after FPUF waste.…”
Section: Introductionmentioning
confidence: 99%